The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/healthcare10061115
|View full text |Cite
|
Sign up to set email alerts
|

Moving toward Appropriate Motor Assessment Tools in People Affected by Severe Acquired Brain Injury: A Scoping Review with Clinical Advices

Abstract: Severe acquired brain injury (SABI) is among the leading causes of death and disability worldwide. Patients following SABI may develop motor, sensory and cognitive disorders, alone or in combination. This review aims to point out the most used scales to assess motor function in SABI patients, also attempting to give some indications on their applicability in clinical practice. Studies were identified by searching on PubMed, Web of Science, PeDro and Cochrane databases between January and March 2022. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…Among the survivors of moderate to severe head injury, 31.8% of patients die or need hospitalization in a specialized health center, 44% are unable to return to work, and 88% of the patients with mild TBI have white matter damage, with negative repercussions on functional outcomes [ 5 ]. Indeed, TBI is usually identified as mild, moderate, or severe through diagnostic and prognostic clinical scales [ 6 ], such as the Glasgow Coma Scale, which measures the level of injury in relation to the loss of consciousness, memory loss, or type of responses to different levels of verbal or not stimuli [ 7 ]. The treatments for TBI depend on many factors, including the size, severity, and location of the brain injury [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the survivors of moderate to severe head injury, 31.8% of patients die or need hospitalization in a specialized health center, 44% are unable to return to work, and 88% of the patients with mild TBI have white matter damage, with negative repercussions on functional outcomes [ 5 ]. Indeed, TBI is usually identified as mild, moderate, or severe through diagnostic and prognostic clinical scales [ 6 ], such as the Glasgow Coma Scale, which measures the level of injury in relation to the loss of consciousness, memory loss, or type of responses to different levels of verbal or not stimuli [ 7 ]. The treatments for TBI depend on many factors, including the size, severity, and location of the brain injury [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we need to devote more attention to observational and intervention studies in this field in the future. It is crucial to aid in the functional recovery of patients with DoC and establish a correct prognosis ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Modified Ashworth Scale (MAS) is, in fact, the most commonly used clinical tool for assessing spasticity. However, it does have several limitations [39]. Indeed, de-la-Torre et al [38] in their systematic review found that R-AMA based on data capture is effective for evaluating spasticity.…”
Section: Robotic Devices For Upper Limb Measurementmentioning
confidence: 99%